An analysis of the tourist demand of Pehuen Có (Argentina) in times of post-pandemic - Gambarota, Daniela Melisa (2023)
Since the emergence of COVID-19, one of the sectors most affected has been tourism. However, the scenario and measures such as restrictions of movement abroad, led to a growth of regional tourism. The objective of this research is to determine how the COVID-19 pandemic has affected the tourist demand of Pehuen Có (Argentina). From there, the opportunity arises to position itself as a regional tourist destination considering the proximity to Bahía Blanca and the attractions that the resort has. The methodology consists of a bibliographic review of relevant concepts, a characterization of the town and an analysis of the surveys carried out by the Tourism Directorate of Coronel Rosales in the summer periods from 2015 to 2021 (between 900 and 1200 annually), considering a sample error of 3%. The results show that Pehuen Có has greater resilience than other tourist destinations and has competitive advantages in the post-pandemic tourism context. The conclusion reached is that the pandemic has been an opportunity to revalue local tourist spaces, with proposals focused on the development of creative, sustainable and responsible tourism.